Green Burial, Home Burial: A Return to Redbud Hill - Bayer, Ellen M (The Trumpeter)

(untitled) (Athabasca University Press, 2018)
This paper uses my own personal journey toward a green home burial as a vehicle for exploring this emerging industry. A recent move across the country prompted me to reflect upon my own burial place. While I have known for years that I would prefer a green burial, the transition from my native Midwest to the Pacific Northwest was a catalyst for anxieties about leaving the familiar for a foreign (to me) landscape. Knowing that my body would one day return to the hills of my childhood provided a strange sense of calm, but a cursory look into the prospects of a home burial on my 18 acres in rural Indiana suggested the logistics were more complicated than I imagined. I learned that Indiana is one of only five states that do not allow home burial, or that have highly restrictive laws governing it. What had promised to be a simple and natural end of life decision spiraled into a bureaucratic labyrinth. Blending insights into the green burial movement with a navigation of my own experience, this paper seeks to demonstrate the environmental and personal benefits of natural burial practices while also unearthing factors that complicate its accessibility.